Pengaruh Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM yang Dimoderasi Melalui Motivasi Wajib Pajak Dalam Melaksanakan Kewajiban Perpajakan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
On June 8, 2018, the government issued Government Regulation Number 23 to replace Government Regulation Number 46 of 2013, as it was deemed too burdensome for taxpayers with unstable gross income. This replacement certainly changed the Final Income Tax rate from the initial 1% to 0.5%. In this research, variables include Tax Knowledge, Tax Compliance, and Taxpayer Motivation. The research method employed a descriptive-verification approach through interview surveys and questionnaires. The findings indicate that tax knowledge does not have a significant influence on taxpayer compliance. However, the analysis with the t-test shows a t-value significance of 0.189, which is greater (>) than 0.05. Nevertheless, taxpayer motivation has a significant impact on strengthening the relationship between tax understanding and taxpayer compliance, as the t-test result shows a significance value of 0.021, which is smaller (<) than 0.05.